Programa psicoeducativo para disminuir los efectos emocionales de los niños como consecuencia de la separación de los padres a partir de un análisis documental (2021)
The separation of couples in Colombia and the world is an event that is increasing, this phenomenon refers to not living together and to a legal termination or not of the existing relationship, if we consider the family as a base set for society, it is understood also that any change, whether negative or positive, directly affects the members of the same, in this case the children are mostly affected. The general objective of this research is to design an intervention program with psychoeducational strategies that helps reduce the emotional effects of children as a result of separation from parents, from a qualitative methodology that allows collecting information for documentary analysis and based on a cognitive behavioral psychological approach. The results of the research were according to the 38 articles found in the academic